Encyclopedia of Medical Devices and Instrumentation 2006
DOI: 10.1002/0471732877.emd287
|View full text |Cite
|
Sign up to set email alerts
|

Microbioreactors

Abstract: Recent advances in micro‐ and nanotechnologies coupled with the need in biology and medicine to perform cellular scale studies and productions have led to the emergence of a variety of microscale biological reaction systems. These microbioreactors are promising as low cost modules for optimizing bioproduction processes, highly parallel analytical platforms for screening pharmaceutical drugs, therapeutic implements for treating disorders and deficiencies, and examination tools for exploring basic physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 197 publications
0
7
0
Order By: Relevance
“…More recently, fluorescent nanoparticles have been used as labels for cell based assays. Fluorescent quantum dots nanomaterials are useful probes for many types of cell labeling in that they can be used for measuring cell viability by fluorescence techniques [26]. However, some studies have demonstrated that nanomaterials induce stress responses in some mammalian cells.…”
Section: Optical Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, fluorescent nanoparticles have been used as labels for cell based assays. Fluorescent quantum dots nanomaterials are useful probes for many types of cell labeling in that they can be used for measuring cell viability by fluorescence techniques [26]. However, some studies have demonstrated that nanomaterials induce stress responses in some mammalian cells.…”
Section: Optical Methodsmentioning
confidence: 99%
“…The absence of moving parts, lower complexity and fabrication costs as well as being less prone to breakdown due to fatigue are considered as the key advantages of using passive microvalves in microfluidic application [26]. These types of microvalves restrict the flow of fluids in a single direction and can take the form of polymer based check valves, passive valves based on surface tension and hydrogel based biomimetic valves [115].…”
Section: Microvalvesmentioning
confidence: 99%
See 3 more Smart Citations